PENGARUH MEDIA SOSIAL TIKTOK TERHADAP MINAT BERKUNJUNG WISATAWAN NUSANTARA KE DESTINASI KLADI GLAMPING KINTAMANI: PENGARUH MEDIA SOSIAL TIKTOK TERHADAP MINAT BERKUNJUNG WISATAWAN NUSANTARA KE DESTINASI KLADI GLAMPING KINTAMANI - I Gusti Ngurah Agung Rama Wijaya; I Made Subrata (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study aims to analyze the influence of TikTok social media on the visiting intention of domestic tourists to the Kladi Glamping tourism destination in Kintamani, Bangli Regency. The influence of social media is examined both simultaneously and partially through five dimensions of social media engagement, namely Participation, Openness, Conversation, Community, and Connectedness. This research employs a quantitative approach with a simple linear regression analysis method using SPSS software as the analytical tool. Data were collected from 125 domestic tourists who had accessed or interacted with TikTok content related to the Kladi Glamping destination. The results of the analysis indicate that TikTok social media has a significant positive influence on tourists’ visiting intention. This is evidenced by a t-value of 8.855, which exceeds the t-table value of 1.979, and a significance level of 0.000, which is lower than the threshold of 0.05. These findings demonstrate that TikTok serves as an effective promotional medium in shaping tourists’ interest and intention to visit glamping destinations, particularly among domestic tourists. Furthermore, the frequency analysis of each construct reveals that while TikTok content has successfully attracted attention and engagement, there remain aspects that require improvement, especially in terms of physical environmental arrangement and service quality at the destination. Therefore, it is recommended that destination managers optimize the use of TikTok by presenting more informative, interactive, and authentic content, while simultaneously improving on-site facilities and services to enhance tourists’ overall experience. The findings of this study are expected to contribute to the development of digital marketing strategies in tourism, particularly in utilizing social media platforms to increase tourist visitation to glamping destinations.